2019
DOI: 10.1002/chem.201900042
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Target of a Rhodium Metalloinsertor is the DNA Base Pair Mismatch

Abstract: Defects in DNA mismatchrepair (MMR) are commonly found in various cancers, especially in colorectal cancers. Despite the high prevalence of MMR-deficient cancers, mismatch-targeted therapeuticsa re limited and diagnostic tools are indirect. Here, we examine the cytotoxic properties of ar hodiummetalloinsertor, [Rh(phen)(chrysi)(PPO)] 2 + (RhPPO)i n2 7d iversec olorectal cancer cell lines. Despite the low frequency of genomic mismatches and the non-covalentn ature of the RhPPO-DNA lesion, RhPPO is on average fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…Furthermore, a study assessing the cytotoxicity of Rh-PPO in 27 CRC cell lines spanning the four subtypes of CRC, as well as both MMR-deficient and MMR-proficient phenotypes, provided additional support to the hypothesis that the targets of Rh-PPO are DNA base-pair mismatches (23,24). Rh-PPO was found to be on average five times more potent than the Food and Drug Administration (FDA)-approved chemotherapeutic cisplatin with mean IC 50 values (50% inhibitory concentration) of 2.9 μM and 13.2 μM, respectively, across CRC cell lines.…”
Section: Significancementioning
confidence: 88%
“…Furthermore, a study assessing the cytotoxicity of Rh-PPO in 27 CRC cell lines spanning the four subtypes of CRC, as well as both MMR-deficient and MMR-proficient phenotypes, provided additional support to the hypothesis that the targets of Rh-PPO are DNA base-pair mismatches (23,24). Rh-PPO was found to be on average five times more potent than the Food and Drug Administration (FDA)-approved chemotherapeutic cisplatin with mean IC 50 values (50% inhibitory concentration) of 2.9 μM and 13.2 μM, respectively, across CRC cell lines.…”
Section: Significancementioning
confidence: 88%
“…In the area of designing small molecules to bind non-canonical DNA structures, DNA mismatch-interactive compounds have shown encouraging preferential activity towards MMR-decient colorectal cancers. 44 While denitive data on the lifetime of mismatches themselves (as opposed to their mutation signatures) in human cells is currently lacking, a genome-wide study in yeast indicated repair of TT mismatches to be one of the least efficient of all mismatch base pairings. 12 Preferential stabilisation of a TT mismatch is a relatively rare nding for mismatchinteractive compounds described to date.…”
Section: Discussionmentioning
confidence: 99%
“…The preferential cytotoxicity of RhPPO-Cy3 for MMRdeficient cells was also observed against other CRC cell lines (Supplemental Information, Figure S10). 24 In co-staining experiments with phospho-H2AX, the nuclear RhPPO-Cy3 foci exhibited partial overlap with phospho-H2AX foci (20 + 4%) ( Figure 3B), suggesting that the DNA lesions formed by RhPPO-Cy3 binding occur at or near sites of DNA mismatches.…”
Section: Biochemistrymentioning
confidence: 96%
“…Phospho-H2AX, as a component of chromatin, spans megabases of DNA surrounding a DNA break. 32 To explore further the potential colocalization of RhPPO-Cy3 with DNA damage foci, we compared RhPPO-Cy3 nuclear localization to that of intensity that correlated with the presence of DNA mismatches and with RhPPO cytotoxicity 24 . In the current study, we directly labeled RhPPO with a fluorescent…”
Section: Biochemistrymentioning
confidence: 99%
See 1 more Smart Citation